Koleksi peralatan dapur tradisional Museum Negeri La Galigo, Ujung Pandang - Data, Muh. Yamin (Seri permuseuman., 1987)
On traditional kitchen of Sulawesi Selatan; includes catalog of the collection of kitchen utensils in the provincial museum of Ujung Pandang.